The Effect of Hyoscine Butylbromide on the First State of Labor in Multiparous Women - Sekhavat, Leila; Karbasi, Sedighah Akhavan (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v4i2.5045 NJOG 2010 Jan-Feb; 4(2): 40-43